A rapid spin through oil results in higher cell-associated concentrations of antiretrovirals compared with conventional cell washing. (July 2015) - Cory, Theodore J; Winchester, Lee C; Robbins, Brian L; Fletcher, Courtney V
Background: Determination of cell-associated antiretroviral drug concentrations is necessary for research into reservoirs of HIV. Variation exists in cell-associated drug concentrations among research groups. One cause for this may be washing cells during processing. We explored spinning cells through oil to minimize this variability.Methods & results: Raltegravir, atazanavir, darunavir, efavirenz, lopinavir and ritonavir concentrations were assessed in CEM.ss T cells washed with HBSS and oil-spun cells. Oil-spun cells had significantly higher concentrations for all drugs compared with samples washed with HBSS.Conclusion: The decline in cell-associated drug concentrations with saline washes compared with a single spin through oil shows the utility of a spin through oil. Oil centrifugation results in high cell-associated drug concentrations, and can be done in a fast, efficient manner.